Plasma membrane protein trafficking in plant–microbe interactions: a plant cell point of view - Nathalie Leborgne-Castel,; Bouhidel, Karim (Frontiers in Plant Science, 2014)
In order to ensure their physiological and cellular functions, plasma membrane (PM) proteins must be properly conveyed from their site of synthesis, i.e. the endoplasmic reticulum, to their final destination, the PM, through the secretory pathway. PM protein homeostasis also relies on recycling and/or degradation, two processes that are initiated by endocytosis. Vesicular membrane trafficking events to and from the PM have been shown to be altered when plant cells are exposed to mutualistic or pathogenic microbes. In this review, we will describe the fine-tune regulation of such alterations, and their consequence in PM protein activity. We will consider the formation of intracellular perimicrobial compartments, the PM protein trafficking machinery of the host, and the delivery or retrieval of signaling and transport proteins such as pattern-recognition receptors, producers of reactive oxygen species, and sugar transporters.